Influence of the combination and phase variation status of the haemoglobin receptors HmbR and HpuAB on meningococcal virulence - Tauseef, Isfahan; Harrison, Odile B; Wooldridge, Karl G; Feavers, Ian M; Neal, Keith R; Gray, Stephen J; Kriz, Paula; Turner, David P J; Ala'Aldeen, Dlawer A A; Maiden, Martin C J; Bayliss, Christopher D; Shaw, J G (Microbiology (Reading, England), 2011)
Neisseria meningitidis can utilize haem, haemoglobin and haemoglobin-haptoglobin complexes as sources of iron via two TonB-dependent phase variable haemoglobin receptors, HmbR and HpuAB. HmbR is over-represented in disease isolates, suggesting a link between haemoglobin acquisition and meningococcal disease. This study compared the distribution of HpuAB and phase variation (PV) status of both receptors in disease and carriage isolates. Meningococcal disease (n = 214) and carriage (n = 305) isolates representative of multiple clonal complexes (CCs) were investigated for the distribution, polyG tract lengths and ON/OFF status of both haemoglobin receptors, and for the deletion mechanism for HpuAB. Strains with both receptors or only hmbR were present at similar frequencies among meningococcal disease isolates as compared with carriage isolates. However, >90 % of isolates from the three CCs CC5, CC8 and CC11 with the highest disease to carriage ratios contained both receptors. Strains with an hpuAB-only phenotype were under-represented among disease isolates, suggesting selection against this receptor during systemic disease, possibly due to the receptor having a high level of immunogenicity or being inefficient in acquisition of iron during systemic spread. Absence of hpuAB resulted from either complete deletion or replacement by an insertion element. In an examination of PV status, one or both receptors were found in an ON state in 91 % of disease and 71 % of carriage isolates. We suggest that expression of a haemoglobin receptor, either HmbR or HpuAB, is of major importance for systemic spread of meningococci, and that the presence of both receptors contributes to virulence in some strains.
Keywords: Virulence; Gene Expression Regulation, Bacterial; proteiny vnější bakteriální membrány; železo; bakteriální proteiny; Bacterial Proteins; meningokokové infekce; Bacterial Outer Membrane Proteins; Carrier State; Molecular Sequence Data; Meningococcal Infections; regulace genové exprese u bakterií; virulence; přenašečství; molekulární sekvence - údaje; Iron; Neisseria meningitidis; receptory buněčného povrchu; Receptors, Cell Surface